Highly Sensitive Detection and Mapping of Incipient and Steady-State Oxygen Evolution from Operating Li-Ion Battery Cathodes via Scanning Electrochemical Microscopy. Issue 8 (1st August 2022) - Mishra, Abhiroop; Sarbapalli, Dipobrato; Hossain, Md. Sazzad; Gossage, Zachary T.; Li, Zheng; Urban, Alexander; Rodríguez-López, Joaquín
Abstract : Lattice oxygen loss during cathode charging significantly limits the charge storage capacity of lithium-ion batteries (LiBs). Therefore, elucidating the oxygen loss and subsequent surface reconstruction phenomena remains an ongoing pursuit with practical implications. In this article, we report an in situ oxygen detection strategy using scanning electrochemical microscopy (SECM) that reveals an unprecedented two-stage oxygen evolution behavior from commercial cathodes. This highly sensitive SECM method captured an unreported transient oxygen release at less than 3.3 V vs Li + /Li during the first charge cycle of LiCoO2, LiNi0.33 Mn0.33 Co0.33 O2 and LiNi0.8 Mn0.1 Co0.1 O2 . At the main oxygen loss process above 3.3 V vs Li + /Li, SECM mapping highlighted spatial and temporal heterogeneities. Finite element simulations were used to quantify the rate of instantaneous oxygen release, with rates of ∼30 pmol cm −2 s for the steady-state oxygen evolution. This SECM approach revealed incipient degradation processes and created new quantitative and spatially resolved opportunities for investigating degradation in operating LiB cathodes.